Eksplorasi Energi Biogas di PT. Biro Teknik Sinar Baru - Iswahyudi, Iswahyudi; Sutikno, Sutikno; Auliq, M A’an; Ariyani, Sofia; Sofia, Deni (Journal of Mechanical Engineering, 2024)
Energy sources originating from fossil fuels such as petroleum, coal and others cause environmental damage and increase greenhouse gases. Cow dung is a renewable energy source that is rarely used but has many benefits after being produced into biogas which can be used as electricity and gas. The advantages of using livestock manure into biogas include renewable energy, biogas can reduce environmental pollution and reduce greenhouse emissions. In this research, we studied biogas energy exploration at PT Bureau Teknik Sinar Baru. A comparative study of the potential of biogas and LPG from several aspects, namely duration, volume of use, CO gas, and cost, has been carried out with the aim of evaluating the advantages and limitations of each of these energy sources. Based on the test results, biogas is 14 minutes faster, more economical 0.05 liters, and the CO gas produced is 0.20% - 0.33% smaller than LPG for boiling 5 liters of water. In conclusion, this study shows that biogas has the potential to be a cheaper, environmentally friendly and sustainable alternative energy source compared to LPG.